Cardiac Troponin I Associated with the Development of Unrecognized Myocardial Infarctions Detected with MRI. (1st October 2014) - Barbier, Charlotte Ebeling; Themudo, Raquel; Bjerner, Tomas; Johansson, Lars; Lindahl, Bertil; Venge, Per; Lind, Lars; Ahlström, Håkan
Abstract: BACKGROUND: Late enhancement MRI (LE-MRI) and cardiac troponin I (cTnI) are sensitive methods to detect subclinical myocardial injury. We sought to investigate the relation between plasma concentrations of cTnI measured with a high-sensitivity assay (hs-cTnI) and the development of unrecognized myocardial infarctions (UMIs) detected with LE-MRI. METHODS: After approval from the ethics committee and written informed consent were obtained, LE-MRI was performed on 248 randomly selected community-living 70-year-old volunteers and hs-cTnI was determined with a highly sensitive premarket assay. Five years later these individuals were invited to a second LE-MRI, and 176 of them (82 women, 94 men), who did not have a hospital diagnosis of MI, constitute the present study population. LE-MR images were analyzed by 2 radiologists independently and in a consensus reading, blinded to any information on previous disease or assessments. RESULTS: New or larger UMIs were detected in 37 participants during follow-up. Plasma concentrations of hs-cTnI at 70 years of age, which were mainly within what is considered to be the reference interval, were related to new or larger UMIs at 75 years of age with an odds ratio of 1.98 per 1 unit increase in ln-transformed cTnI (95% CI, 1.17–3.35; P = 0.010). Plasma concentrations of hs-cTnI at 70 years of age were associated with the volumes of the UMIs detected at 75 years of age ( P = 0.028). CONCLUSIONS: hs-cTnI in 70-year-old community-living women and men was associated with the development of MRI-detected UMIs within 5 years.